A rock and an art place: the Inkas' Collaconcho in context. Issue 3 (2nd September 2019) - Dean, Carolyn
Abstract : Collaconcho, a large rocky outcropping located at the edge of the Inka archaeological site of Saqsaywaman, was – from an Andean perspective – both sentient and agentic. Oral histories accuse this stone of resisting Inka construction efforts and also of homicide. Over time, Inka stone carvers blanketed its surface with mostly abstract forms; of them, step motifs ( siqana ) predominate. Here we consider the significance of Collaconcho's 'steps' and what this outcropping meant to the Inkas who made it and to the indigenous Andeans who viewed it. Bearing in mind Collaconcho's location and the legend surrounding it, I suggest that its carvings may be dialogic in nature, that the Inkas sculpted the rock as a means of communicating with this venerable, powerful, and – at times – hostile being. Collaconcho, in its storied defiance and heavily carved superficies, embodied the ways the Inkas engaged oppositional forces.